Al-ʿAnāṣir al-Jawhariyyah fī Fīlm “Suʿād” li-Āytīm Amīn (Dirāsah Taḥlīliyyah fī ʿIlm al-Ādāb) - Dini Hariyati Kurniatillah; Sri Sudiarti (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
This article is derived from an undergraduate thesis that analyzes the intrinsic elements of the film Suad (2021) directed by Ayten Amin using a structuralist approach. The study aims to examine how intrinsic elements-namely theme, characters and characterization, plot, setting, point of view, language style, and moral message-interact to construct the overall meaning of the film. This research employs a qualitative descriptive method with a library research design. The primary data source is the film Suad, while secondary data consist of books, academic journals, and previous studies related to structuralism and film analysis. The findings reveal that the central theme of the film is the search for identity and psychological alienation experienced by an adolescent girl within a conservative social environment. The main character is portrayed through strong psychological characterization, supported by a linear plot that emphasizes everyday routines and emotional tension. The setting, both spatial and temporal, reflects social pressure and emotional isolation, while the limited third-person point of view allows viewers to observe the character’s inner conflict without explicit moral judgment. The language style is realistic and minimalist, relying heavily on visual expression and silence rather than dialogue. Overall, the film conveys a profound moral message concerning the importance of empathy, emotional support, and mental health awareness, particularly for adolescents. This study concludes that Suad presents a coherent structural unity in which intrinsic elements function synergistically to deliver a strong social and psychological critique.